Economic Aspects of Energy Production, Distribution and Consumption - Jacek Strojny; Piotr Kacorzyk (Energies)
In a dynamically changing socio-economic environment, the key factors driving the development of the modern economy and social progress are financial aspects, access to markets, technological innovations and ensuring access to energy [...]